Differences In Students Problem Solving and Mathematical Creative Thinking Skills Using Problem Based Learning and Inquiry Models - Nasution, Siti Khodijah (Yana Research, 2022)
This study aims to determine the difference between Problem Solving Ability and Mathematical Creative Thinking Ability of Students by Using Problem Based Learning and Inquiry Models. The assessment was carried out on the tenth grade students of SMA Private Nurul Islam Indonesia, Medan. The sample was determined by cluster random sampling. This research is a quantitative research with a quasi-experimental type of research, and the test instrument used in this research is in the form of a description. From the results of data research using Analysis of Variance (ANAVA), the findings show: 1). Mathematical Problem Solving Ability of students who are taught using the Problem Based Learning model is better than students who are taught using the Inquiry model on SPLTV material seen in the value of Fcount = 10,480, and the value in Ftable at the level of (0,05) = 4,001. This means that Fcount > Ftable; 2). Mathematical Creative Thinking Ability of students who are taught using the Problem Based Learning model is better than students who are taught using the Inquiry model on SPLTV material seen in the Fcount = 8,574, and the value in Ftable at the level (0,05) = 4,001. This means that Fcount > Ftable; 3). Problem Solving Ability and Mathematical Creative Thinking Ability of students who are taught with the Problem Based Learning model are not better than students who are taught with the Inquiry model on SPLTV material Fcount = 0.415, Ftable at level (0.05) = 3.920. This means that Fcount< Ftable. The conclusion of the study explains that there is no difference in Problem Solving Ability and Mathematical Creative Thinking Ability of students who are taught with Problem Based Learning and Inquiry Learning Models.